1989
DOI: 10.1177/0310057x8901700202
|View full text |Cite
|
Sign up to set email alerts
|

Open Cardiac Compression in the Postoperative Cardiac Intensive Care Unit

Abstract: Thirty-nine patients required heroic resuscitative measures for sudden hypotension and cardiac arrest in the first 72 hours following cardiac surgery between January 1, 1984 and May 31, 1988. Emergency sternotomy with open cardiac compression was performed in twenty-four of these patients when external cardiac compression failed. These were categorised as Group A. Group B comprised the fifteen patients in whom resuscitation was entirely by means of external compression and adjuvant measures. Survival with NYHA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 10 publications
(4 reference statements)
0
8
0
1
Order By: Relevance
“…Potential Trauma Induced by ECM Потенциальные травмы, вызванные НМС We identified 4 patients in the cardiothoracic literature who had massive hemorrhage after external cardiac massage [27,28]. However, several cohort studies of patients receiving ECM after cardiac surgery documented that no injuries were seen due to that in their series [10,29]. В литературе, посвященной кардиоторакальной тематике, нам удалось найти 4 случая массивного кровотечения после НМС [27,28].…”
Section: English Russianmentioning
confidence: 99%
“…Potential Trauma Induced by ECM Потенциальные травмы, вызванные НМС We identified 4 patients in the cardiothoracic literature who had massive hemorrhage after external cardiac massage [27,28]. However, several cohort studies of patients receiving ECM after cardiac surgery documented that no injuries were seen due to that in their series [10,29]. В литературе, посвященной кардиоторакальной тематике, нам удалось найти 4 случая массивного кровотечения после НМС [27,28].…”
Section: English Russianmentioning
confidence: 99%
“…Several studies of open-chest CPR have demonstrated improved coronary perfusion pressure and/or return of spontaneous circulation (ROSC) for both the inhospital (eg, following cardiac surgery) 46 and out-of-hospital environments. 710 …”
Section: Cpr Techniquesmentioning
confidence: 99%
“…El-Banayosy et al [14] reported 113 patients who had 20 or more minutes of ECM, with a survival of 70% without any ECM-attributable complications. Raman et al [67] reported 39 patients with cardiac arrest after cardiac surgery. Emergency resternotomy was performed in 24 and the authors specifically stated that 'no significant damage to the myocardium was considered to have occurred as a result of direct cardiac compression.…”
Section: Reports On Trauma Induced By Ecmmentioning
confidence: 99%
“…No mention of antibiotic use was given. Ramen et al [67] reported 39 patients who arrested after cardiac surgery. An emergency resternotomy was performed in 21 patients with povidone-iodine skin preparation, aseptic reopening on the ICU and perioperative antibiotics for 48 h. In addition, patients were returned to theatre for povidone-iodine washout and closure.…”
Section: Should Patients Receive Additional Antibiotics After Emergenmentioning
confidence: 99%